Cancer patients' emotional distress, coping styles and perception of doctor-patient interaction in European cancer settings*. Issue 3 (9th July 2015) - Meggiolaro, Elena; Berardi, Maria Alejandra; Andritsch, Elisabeth; Nanni, Maria Giulia; Sirgo, Agustina; Samorì, Elena; Farkas, Clemens; Ruffilli, Federica; Caruso, Rosangela; Bellé, Marta; Juan Linares, Eva; de Padova, Silvia; et al.
Abstract: Objective: As a part of a European study, we cross-culturally examined the rate of emotional distress and maladaptive coping and their association with cancer patients' satisfaction with their interactions with the physician responsible for their care. Methods: Cancer patients (n = 302) from one Middle European (Austria) and two Southern European (Italy, Spain) countries completed the NCCN Distress Thermometer (DT), the Mini-Mental Adjustment to Cancer (Mini-MAC) Anxious Preoccupation (AP) and Hopelessness (H) sub-scales, and the Physician Patient Satisfaction with Doctors Questionnaire (PSQ). Results: The prevalence of emotional distress (DT caseness) was 60% (26.1% mild, 18.8% moderate, and 14.9% severe distress). Maladaptive coping (Mini-MAC cases) was found in 22.8% (hopeless cases), and 22.5% (anxious preoccupation cases). PSQ-MD was significantly correlated with Mini-MAC/H and Mini-Mac/AP, while PSQ-PS was negatively correlated with Mini-MAC/H. DT cases and those with higher levels of hopelessness reported higher scores on PSQ-MD and lower on PSQ-PS than non-cases. Some differences were found between countries both as far as patients' coping and perception of the interaction with doctors. In hierarchical multiple regression analysis, after adjusting for socio-demographic and medical variables, Mini-MAC/H significantly predicted the scores on PSQ-MD (positive direction) and PSQ-PS (negative direction). Significance of results: The study confirms that about one out of three cancer patients have moderate to high level of emotional distress and about one out of four, clinically significant maladaptive coping. Also, patients showing hopelessness and distress tended to perceive their doctors as both disengaged and less supportive. These results highlights the need for physicians to monitor their patient's level of distress and coping mechanisms and to adjust their own relational and communication style according to patients' psychological condition. Also, cross-cultural issues should be taken into account when exploring psychosocial variables and cancer patients' perception of and satisfaction with the interaction with their doctors.